Illicit Stimulant Use in Humans Is Associated with a Long-Term Increase in Tremor - Flavel, Stanley C. (Public Library of Science, 2012)
Use of illicit stimulants such as methamphetamine, cocaine, and ecstasy is a significant health problem. The United Nations Office on Drugs and Crime estimates that 14–57 million people use stimulants each year. Chronic use of illicit stimulants can cause neurotoxicity in animals and humans but the long-term functional consequences are not well understood. Stimulant users self-report problems with tremor whilst abstinent. Thus, the aim of the current study was to investigate the long-term effect of stimulant use on human tremor during rest and movement. We hypothesized that individuals with a history of stimulant use would exhibit abnormally large tremor during rest and movement. Tremor was assessed in abstinent ecstasy users (n = 9; 22±3 yrs) and abstinent users of amphetamine-like drugs (n = 7; 33±9 yrs) and in two control groups: non-drug users (n = 23; 27±8 yrs) and cannabis users (n = 12; 24±7 yrs). Tremor was measured with an accelerometer attached to the index finger at rest (30 s) and during flexion and extension of the index finger (30 s). Acceleration traces were analyzed with fast-Fourier transform. During movement, tremor amplitude was significantly greater in ecstasy users than in non-drug users (frequency range 3.9–13.3 Hz; P<0.05), but was unaffected in cannabis users or users of amphetamine-like drugs. The peak frequency of tremor did not significantly differ between groups nor did resting tremor. In conclusion, abstinent ecstasy users exhibit an abnormally large tremor during movement. Further work is required to determine if the abnormality translates to increased risk of movement disorders in this population.